Perspective of Primigravida Mother’s Experience in Their Birthing Process Utilising HypnoBirthing - Paramasivam, Thavamalar; Mariappan, Umapathi; Chong, Mei Chan (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Child birth can be an enjoyable process for all birthing women. Use of HypnoBirthing®Mongan during birthing process induces the women to be relaxed and minimises her fear. The aim of the research is to explore the perspective of primigravida mother’s experience in their birthing process utilising hypnobirthing. Methods: A qualitative study involving 10 participants was carried out in a private hospital in Malaysia. Purposive sampling was used. Women using HypnoBirthing during birthing were interviewed for 40 minutes using semi structured, face to face method. Analysed using thematic analysis. Results: Three main themes were identified namely: ‘physical and emotional effect of pain’, ‘behaviour response to pain’ and ‘maternal and newborn wellbeing’. Physical and emotional effect of pain has four subthemes where else the other has two subthemes. Conclusion: Women using Hypnobirthing enjoyed the birthing process and immediate bonding with the newborn. REFERENCES Luce A, Cash M, Hundley V, Cheyne H, Van Teijlingen E, Angell C. “Is it realistic?” the portrayal of pregnancy and childbirth in the media. BMC Pregnancy and Childbirth. 2016;16:1-10. https://doi.org/10.1186/s12884-016-0827-x[<a href="https://scholar.google.com/scholar_lookup?title=Luce+A%2C+Cash+M%2C+Hundley+V%2C+Cheyne+H%2C+Van+Teijlingen+E%2C+Angell+C.+%E2%80%9CIs+it+realistic%3F%E2%80%9D+the+portrayal+of+pregnancy+and+childbirth+in+the+media&btnG=">Google Scholar][Pubmed] Miller Y, Danoy-Monet M. Reproducing fear: the effect of birth stories on nulligravid women’s birth preferences. BMC Pregnancy and Childbirth. 2021;21:1-13. https://doi.org/10.1186/s12884-021-03944-w.[Google Scholar] [PMC free article] [Pubmed] Thompson T, Terhune DB, Oram C, Sharangparni J, Rouf R, Solmi M, Veronese N, Stubbs B. The effectiveness of hypnosis for pain relief: A systematic review and meta-analysis of 85 controlled experimental trials. Neuroscience & Biobehavioral Reviews. 2019 04;99:298-310. https://doi.org/10.1016/j.neubiorev.2019.02.013[Google Scholar][Pubmed][Crossref] Mongan M. HypnoBirthing® The Mongan Method: A natural approach to a safe, easier, more comfortable birthing. 2005;.[Google Scholar] Paramasivam T, Mariappan U, Chan C. Mixed-Method Pilot Study: Effectiveness of HypnoBirthing in Labour Outcomes. Enhancing Capacity of Healthcare Scholars and professionals in Responding to the Global Health Issues. 2019. 2019. 2020;:1-11. https://doi.org/10.2478/9783110680041-001[Google Scholar] Steel A, Adams J, Sibbritt D, Broom A. The Outcomes of Complementary and Alternative Medicine Use among Pregnant and Birthing Women: Current Trends and Future Directions. Women's Health. 2015 05;11(3):309-323. https://doi.org/10.2217/whe.14.84[Google Scholar][Pubmed] Oltmann S. Qualitative Interviews: A Methodological Discussion of the Interviewer and Respondent Contexts. Forum: Qualitative Social Research. 2016;17:1-12. https://doi.org/10.17169/fqs-17.2.2551[Google Scholar] Bryman A. Social research methods. 3rd Edition. USA: Oxford University Press. 2008;.[Google Scholar] Maguire M, Delahunt B. Doing a Thematic Analysis: A Practical, Step-by-Step Guide for Learning and Teaching Scholars. All Ireland Journal of Teaching and Learning in Higher Education. 2017;8:3351-33514.[Google Scholar] Liang M, Mouraux A, Iannetti G. Parallel Processing of Nociceptive and Non-nociceptive Somatosensory Information in the Human Primary and Secondary Somatosensory Cortices: Evidence from Dynamic Causal Modeling of Functional Magnetic Resonance Imaging Data. Journal of Neuroscience. 2011;31:8976-85. https://doi.org/10.1523/JNEUROSCI.6207-10.2011[<a href="https://scholar.google.com/scholar_lookup?title=Parallel+Processing+of+Nociceptive+and+Non-nociceptive+Somatosensory+Information+in+the+Human+Primary+and+Secondary+Somatosensory+Cortices%3A+Evidence+from+Dynamic+Causal+Modeling+of+Functional+Magnetic+Resonance+Imaging+Data&btnG=">Google Scholar] [PMC free article] [Pubmed] Legiati T, Widiawati I. Hypnobirthing effect on the level of pain in labour. Jurnal Kesehatan Masyarakat. 2017;13:185-90. https://doi.org/10.15294/kemas.v13i2.6732[Google Scholar] Rahimi F, Goli S, Soltani N, Rezaei H, Amouzeshi Z. Effects of Complementary Therapies on Labor Pain: A Literature Review. Modern Care Journal. 2018;15:1-7. https://doi.org/10.5812/modernc.69306[Google Scholar] James S, Hudek M. Experiences of South African multiparous labouring women using the birthing ball to encourage vaginal births. Health SA Gesondheid. 2017;22:36-42. https://doi.org/10.1016/j.hsag.2016.08.004[Google Scholar][Crossref] Chan C, Wong S, Lam M, Wong Y, Kwok C. An exploration of postpartum women's perspective on desired obstetric nursing qualities. Jounal of Clinical Nursing. 2013;23:103-12. https://doi.org/10.1111/jocn.12093[Google Scholar][Pubmed] Lunda P, Minnie C, Benadé P. Women’s experiences of continuous support during childbirth: a meta-synthesis. BMC Pregnancy and Childbirth. 2018;18:167. https://doi.org/10.1186/s12884-018-1755-8[Google Scholar] [PMC free article] [Pubmed] Catsaros S, Wendland J. Hypnosis-based interventions during pregnancy and childbirth and their impact on women's childbirth experience: A systematic review. Midwifery. May. 2013;84:102666. https://doi.org/10.1016/j.midw.2020.102666.[Google Scholar][Pubmed][Crossref] Werner A, Uldbjerg N, Zachariae R, Wu CS, Nohr EA. Antenatal Hypnosis Training and Childbirth Experience: A Randomized Controlled Trial. Birth. 2013 Dec;40(4):272-280. https://doi.org/10.1111/birt.12071[Google Scholar][Pubmed] Kappas J. Professional hypnotism manual. 2009;. Levett K, Smith C, Bensoussan A, Dahlen H. Complementary therapies for labour and birth study: a randomised controlled trial of antenatal integrative medicine for pain management in labour. BMJ Open. 2016;6:e010691. https://doi.org/10.1136/bmjopen-2015-010691[<a href="https://scholar.google.com/scholar_lookup?title=Complementary+therapies+for+labour+and+birth+study%3A+a+randomised+controlled+trial+of+antenatal+integrative+medicine+for+pain+management+in+labour&btnG=">Google Scholar] [PMC free article] [Pubmed][Crossref] Barnes LJ, Barclay L, Mccaffery K, Aslani P. Complementary medicine products used in pregnancy and lactation and an examination of the information sources accessed pertaining to maternal health literacy: a systematic review of qualitative studies. BMC Complement Altern Med. 2018;18:229. https://doi.org/10.1186/s12906-018-2283-9.[<a style="background-color: #ffffff; font-size: 0.875rem;" href="https://scholar.google.com/scholar_lookup?title=Complementary+medicine+products+used+in+pregnancy+and+lactation+and+an+examination+of+the+information+sources+accessed+pertaining+to+maternal+health+literacy%3A+a+systematic+review+of+qualitative+studies.&btnG=">Google Scholar][Pubmed]